The Effectiveness of Transformational Leadership with Emphasis Optimization Job Characteristics in Enhancing the Employee Performance - Sujoto, Ujo; Moeins, Anoesyirwan; Hamzah (Research Horizon, 2025)
Public service institutions, particularly immigration checkpoints, are facing increasing demands for efficiency and professionalism, making employee performance a critical concern. In this context, leadership style and job design are considered key drivers in enhancing workforce effectiveness. This study aims to examine the effectiveness of transformational leadership and the optimization of job characteristics in improving employee performance at the Soekarno-Hatta Immigration Checkpoint (TPI) under the Directorate General of Immigration. A quantitative research approach was employed using a survey method, with data collected through questionnaires distributed to TPI employees and analyzed using multiple linear regression. The findings reveal that transformational leadership significantly contributes to employee performance by offering inspiration, motivation, and individualized support. Additionally, job characteristics such as skill variety, autonomy, and feedback also have a strong positive effect on enhancing employee engagement and responsibility. Furthermore, both variables collectively exert a significant influence on performance improvement. The study concludes that the synergy between inspirational leadership and well-designed job structures is essential for achieving optimal employee outcomes. These insights offer practical implications for strategic human resource management within public sector organizations.